Plays by George Bernard Shaw - George Bernard Shaw (U.S.A Signet Classic, 2004)
In Mrs. Warren's Profession, Arms and the Man, Candida, and Man and Superman, George Bernard Shaw satirizes society, military heroism, marriage, and the pursuit of man by woman. From a social, literary, and theatrical standpoint, these four plays are among the foremost dramas of the age-as intellectually stimulating as they are humorous.
Keywords: Play, Drama; Play -- Play; Drama -- Drama